Pengaruh FoMO terhadap Gaya Hidup Gen Z Pengguna TikTok - Alya Putri Noviani; Hendika Suryawinata; Siti Rania Maelani; Sri Mulyeni (Jurnal Manajemen Bisnis Era Digital, 2026)
The advancement of social media platforms, especially TikTok, has drastically changed the behavioral patterns and lifestyles of Generation Z. One psychological impact of intensive social media use is Fear of Missing Out (FoMO), which is the worry of missing out on news, trends, or viral social activities. This study aims to reveal how FoMO affects the lifestyle of Generation Z active on TikTok, focusing on aspects of mental health, shopping habits, and the balance of social interactions. This research uses a literature study approach with a qualitative descriptive method, through in-depth analysis of 21 scientific articles published between 2019 and 2025. The findings show that FoMO is associated with increased anxiety, depression, personal dissatisfaction, and excessive social media use among Generation Z. Furthermore, FoMO also drives impulsive consumption patterns and purchases triggered by online trends as well as the desire for social approval. On the other hand, internal factors such as self-confidence and self-control ability have proven to reduce the level of FoMO and its negative effects. This study concludes that FoMO is a complex phenomenon that impacts the mental health and lifestyle of Generation Z, thus requiring measures such as increasing digital literacy, strengthening self-control, and using social media wisely to reduce the negative impacts of FoMO in the long term.